Mechanisms of persistent heavy rainfall related to 10–30‑day oscillation during pre- and post-monsoon-onset periods in the first rainy season over South China - Chunhui Li; Jing Wang; Dejun Gu; Ailan Lin; Bin Zheng; Dongdong Peng; Jinhai He (Climate Dynamics, 2024)

Impact of the winter Arctic sea ice anomaly on the following summer tropical cyclone genesis frequency over the western North Pacific - Shangfeng Chen; Wen Chen; Bin Yu; Liang Wu; Lin Chen; Zhibo Li; Hasi Aru; Jingliang Huangfu (Climate Dynamics, 2023)

A physical analysis of summertime North American heatwaves - Bin Yu; Hai Lin; Ruping Mo; Guilong Li (Climate Dynamics, 2023)
This study examines the dominant heatwave variability over North America (NA), extracted from an empirical orthogonal function (EOF) analysis of summertime monthly warm extreme index anomalies over 1959–2021. The principal mode features a dipole structure with a large area of anomaly over northwestern NA and an anomaly of opposite sign over the southern U.S. The corresponding principal component is associated with a large-scale atmospheric wave train extending from the North Pacific to North America (NP-NA) and a northeastward injection of moisture from the subtropical western Pacific towards western NA, which are key factors in supporting the NA heatwave variability. The NP-NA wave train can be systematically reinforced and supported by synoptic-scale eddies, and may also be forced by an anomalous convection over the tropical-subtropical western Pacific. Surface radiation heating directly contributes to surface temperature anomalies and is dominated by anomalous downwelling shortwave and longwave radiations. In association with a positive phase of the heatwave variability, the NP-NA wave train brings an anticyclonic anomaly over northern NA, leading to anomalous descent, reduced total cloud cover and below-normal precipitation and surface relative humidity over northern NA. Over northwestern NA, the anomalous subsidence causes air to warm through compression. Reduced cloud cover results in increased downward shortwave radiation that is a key contributor to surface radiation heating. In addition, increase in vertically integrated water vapour through the moisture injection from the North Pacific collocates with tropospheric warming. The atmosphere has more water vapor holding capability and acts as a greenhouse gas to absorb longwave radiation, leading to increased downward longwave radiation that is the second major contributor to surface radiation heating. Processes with circulation and surface radiation anomalies of opposite signs will likewise lead to the negative heatwave variability.

The role of internal variability in climate change projections of North American surface air temperature and temperature extremes in CanESM2 large ensemble simulations - Bin Yu; Guilong Li; Shangfeng Chen; Hai Lin (Climate Dynamics, 2020)
Recent studies indicated that the internal climate variability plays an important role in various aspects of projected climate changes on regional and local scales. Here we present results of the spreads in projected trends of wintertime North American surface air temperature and extremes indices of warm and cold days over the next half-century, by analyzing a 50-member large ensemble of climate simulations conducted with CanESM2. CanESM2 simulations confirm the important role of internal variability in projected surface temperature trends as demonstrated in previous studies. Yet the spread in North American warming trends in CanESM2 is generally smaller than those obtained from CCSM3 and ECHAM5 large ensemble simulations. Despite this, large spreads in the climate means as well as climate change trends of North American temperature extremes are apparent in CanESM2, especially in the projected cold day trends. The ensemble mean of forced climate simulations reveals high risks of warm days over the western coast and northern Canada, as well as a weakening belt of cold days extending from Alaska to the northeast US. The individual ensemble members differ from the ensemble mean mainly in magnitude of the warm day trends, but depart considerably from the ensemble mean in spatial pattern and magnitude of the cold day trends. The signal-to-noise ratio pattern of the warm day trend resembles that of the surface air temperature trend, with stronger signals over northern Canada, Alaska, and the southwestern US than the midsection of the continent. The projected cold day patterns reveal strong signals over the southwestern US, northern Canada, and the northeastern US. In addition, the internally generated components of mean and extreme temperature trends exhibit spatial coherences over North America, and are comparable to their externally forced trends. The large-scale atmospheric circulation-induced temperature variability influences these trends. Overall, our results suggest that climate change trends of North American temperature extremes are likely very uncertain and need to be applied with caution.

How can 30–60-day ISO move from the South China Sea to Southern China? - Bin Zheng; Yanyan Huang; Chunhui Li; Ailan Lin (Climate Dynamics, 2020)
In the present study, the northward-propagating intraseasonal oscillations (ISOs) over the South China Sea (SCS) during the summer monsoon season are divided into two types. One is the northward propagation of ISOs confined in the SCS (defined as P1-ISO), another for ISOs moving from the SCS to Southern China (SC) defined as P2-ISO. The spatial and temporal structures of the two types of ISOs are compared based on the analysis of the NCEP–NCAR reanalysis datasets. It is found that a significant difference appears in the heat flux anomalies over SC that is attributed to the cloud-radiation effect. A mechanism associated with the changes in the convective instability is proposed to understand the cause of the northward propagation of the ISO from the SCS to SC. For the P1-ISO, a more precipitation over SC leads to a less surface solar radiation and then a cold land surface temperature (LST), which induces an increase of static stability via surface longwave radiation and sensible heat flux. Whereas the total contribution to the convective instability changes does create an unfavorable for ISOs propagating northward, the moisture convergence, mainly controlled by the baroclinic vorticity advection effect, may contribute to an increase of convective instability that favors the ISOs moving northward. For the P2-ISO, a less precipitation over SC results in a more shortwave radiation reaching the ground that induces a warm LST, and thus leading to a warm low-level air temperature and destabilizing the atmosphere ahead of the convection. Moreover, the moisture convergence, dominated by the warm low-level air temperature, also contributes to the increase of convective instability. Thus the convective instability increment should favor the ISOs moving northward. It is worth noting that the baroclinic vorticity advection and moisture advection are not essential for ISOs propagating from the SCS to SC.

A new DRP-4DVar-based coupled data assimilation system for decadal predictions using a fast online localization technique - Yujun He; Bin Wang; Wenyu Huang; Shiming Xu; Yong Wang; Li Liu; Lijuan Li; Juanjuan Liu; Yongqiang Yu; Yanluan Lin; Xiaomeng Huang; Yiran Peng (Climate Dynamics, 2020)

The dominant role of the atmospheric component of coupled models in ENSO amplitude simulations - Yanli Tang; Lijuan Li; Bin Wang; Pengfei Lin; Lin Chen; Feng Xie; Wenjie Dong; Kun Xia (Climate Dynamics, 2019)

A possible mechanism for the occurrence of wintertime extreme precipitation events over South China - Wenyu Huang; Zifan Yang; Xinsheng He; Daiyu Lin; Bin Wang; Jonathon S. Wright; Ruyan Chen; Wenqian Ma; Feifei Li (Climate Dynamics, 2019)

Interannual variability of Eastern China Summer Rainfall: the origins of the meridional triple and dipole modes - Chao He; Ailan Lin; Dejun Gu; Chunhui Li; Bin Zheng; Tianjun Zhou (Climate Dynamics, 2017)

Formation mechanism for the amplitude of interannual climate variability in subtropical northern hemisphere: relative contributions from the zonal asymmetric mean state and the interannual variability of SST - Chao He; Ailan Lin; Dejun Gu; Chunhui Li; Bin Zheng (Climate Dynamics, 2017)

How much of the interannual variability of East Asian summer rainfall is forced by SST? - Chao He; Bo Wu; Chunhui Li; Ailan Lin; Dejun Gu; Bin Zheng; Tianjun Zhou (Climate Dynamics, 2016)

Relationship between summer rainfall anomalies and sub-seasonal oscillations in South China - Chunhui Li; Tim Li; Ailan Lin; Dejun Gu; Bin Zheng (Climate Dynamics, 2015)